1960
DOI: 10.1111/j.1365-2141.1960.tb06227.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Haemolysis in the Cold‐Haemagglutinin Syndrome

Abstract: arrd Departrirerrt of Rndiotherapy, Hairrrrrersrrrith Hospr'tnl"ALTHOUGH it now seems certain that haeniolysis irr vivo in patients with the cold-hacmagglutinin syndrome is determined by the presence of hgh-thermal amplitude high-titre cold auto-antibodies, the exact way the antibodies bring about the haemolysis has not been completely settled. 111 vitro, adsorption of complement, which with most sera occurs best if they arc acidified to pH 6.5-7.0 (Dacie, 1950(Dacie, , 1955, is most easily demonstrable if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

1961
1961
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 7 publications
(2 reference statements)
2
11
0
1
Order By: Relevance
“…If not ingested, C3bINA cleaves off C3c, and the erythrocyte re-enters the circulation as a partially damaged spherocyte or a completely normal cell. The time-course of C3b inactivation is consistent with the clinical erythrocyte survival studies requiring i to 2 h for the return of the sequestered cells in the circulation (1). These cells may contain immunologically identifiable complement components on their membrane but they are predominantly of the C3d type.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…If not ingested, C3bINA cleaves off C3c, and the erythrocyte re-enters the circulation as a partially damaged spherocyte or a completely normal cell. The time-course of C3b inactivation is consistent with the clinical erythrocyte survival studies requiring i to 2 h for the return of the sequestered cells in the circulation (1). These cells may contain immunologically identifiable complement components on their membrane but they are predominantly of the C3d type.…”
Section: Resultssupporting
confidence: 56%
“…This sequestration was temporary, and the cells began to reappear in the general circulation within 20 min, often entirely reappearing in 3 days. In a patient with chronic cold agglutinin disease, sensitization of autologous erythrocytes in vitro with the patient's antibody produced a rapid clearance of the cells from the circulation, total reappearance within 24 h, and thereafter a normal erythrocyte survival (1). Increasing the extent of complement coating eliminated approximately 30% of the cells, but those reappearing survived normally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lewis, Dacie, and Szur have suggested that cold agglutinin-induced aggregation does not cause red cell damage which persists after the antibody is disassociated from the cell (6). The thermal amplitude of the antibody might be important in determining red cell destruction, either by aggregation or by complement fixation.…”
Section: The Journal Of Clinical Investigation Volume 52 February 1973mentioning
confidence: 99%
“…Large amounts of C3 are fixed to the red cells but the antibody is readily dissociated from the membrane by warming (6). Thus it is possible to examine the C3 attached to the membrane without interference by the presence of antibody.…”
Section: Introductionmentioning
confidence: 99%